Genetic diversity and phylogenetic characteristics of viruses in lily plants in Beijing - Chen, Ling; Guo, Cheng; Yan, Chenge; Sun, Rui; Li, Yongqiang (Frontiers in Microbiology, 2023)
Lily (Lilium) is an important bulbous perennial herb that is frequently infected by one or more viruses. To investigate the diversity of lily viruses, lilies with virus-like symptoms in Beijing were collected to perform small RNA deep sequencing. Then, the 12 complete and six nearly full-length viral genomes, including six known viruses and two novel viruses were determined. Based on sequence and phylogenetic analyses, two novel viruses were considered to be members of the genera Alphaendornavirus (Endornaviridae) and Polerovirus (Solemoviridae). These two novel viruses were provisionally named lily-associated alphaendornavirus 1 (LaEV-1) and lily-associated polerovirus 1 (LaPV-1). Based on sequence, phylogenetic and recombination analyses, strawberry latent ringspot virus (SLRSV) in the genus Stralarivirus (Secoviridae) was identified for the first time in China, and shown to exhibit the highest nucleotide (nt) diversity among the available full-length SLRSV genome sequences, with the highest identities of 79.5% for RNA1 and 80.9% for RNA2. Interestingly, the protease cofactor region in RNA1 was 752 aa in length, whereas those of the other 27 characterized isolates ranged from 700 to 719 aa in length. The genome sequences of lily virus A (potyvirus), lily virus X (Potexvirus) and plantago asiatica mosaic virus (Potexvirus) exhibited varying degrees of sequence diversity at the nucleotide level compared with their corresponding characterized isolates. In addition, PlAMV tended to cluster on a host species-basis. One identified lily mottle virus (Potyvirus) isolate was detected as a recombinant, and which clustered in a different group with four other isolates. Seven identified lily symptomless virus (Carlavirus) isolates, including one recombinant, were clustered into three clades. Our results revealed the genetic diversity of lily-infecting viruses, and sequence insertion, host species and recombination are factors that likely contribute to this diversity. Collectively, our results provide useful information regarding the control of viral disease in lily.